2003
DOI: 10.1177/0020764003049001542
|View full text |Cite
|
Sign up to set email alerts
|

Two Levels of Intervention in Low-Income Women With Depressive Symptoms: Compliance and Programme Assessment

Abstract: The results suggest that both interventions tackle important issues related to depression in women but further data are needed for a better understanding of this relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0
5

Year Published

2004
2004
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 5 publications
2
45
0
5
Order By: Relevance
“…A small study in Mexico (Lara et al 2003) found that addressing issues relevant to Mexican women-issues discovered through earlier work-was not more effective than a 20-minute psychoeducational session. This suggests that tailoring care to population concerns may not be effective if the established elements of care (i.e., CBT or interpersonal therapy techniques) are omitted.…”
Section: Outcomes For Minority Adultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A small study in Mexico (Lara et al 2003) found that addressing issues relevant to Mexican women-issues discovered through earlier work-was not more effective than a 20-minute psychoeducational session. This suggests that tailoring care to population concerns may not be effective if the established elements of care (i.e., CBT or interpersonal therapy techniques) are omitted.…”
Section: Outcomes For Minority Adultsmentioning
confidence: 96%
“…A recent study examined outcomes of depression care in poor women in Mexico (Lara et al 2003). In this study, women were treated with an educational six-week group approach tailored to problems and issues of women in Mexico (Lara et al 1997) as compared with a 20-minute individual psychoeducational meeting.…”
Section: Outcomes Of Mental Health Care For Adults Efficacy Studies Omentioning
confidence: 99%
“…There is a small body of evidence for the efficacy of depression treatment interventions in Latino populations. Several studies, as shown in Table 1, examined depression treatment outcomes among various Latino populations, including Puerto Rican mothers (Comas-Diaz 1981), Mexican women (Lara et al 2003), Puerto Rican adolescents (Rosselló and Bernal 1999), and Spanish speaking IDUs (González et al 1993) with favorable results. Likewise, several successful depression treatment studies with minority samples have had a significant number of Latino participants (Miranda et al 2003 Table 1).…”
Section: Depression and Hiv-positive Latinosmentioning
confidence: 99%
“…Una descripción más amplia sobre las intervenciones puede encontrarse en otros trabajos. [27][28][29] Instrumentos. El equipo de investigación fue capacitado previamente para aplicar, a través de entrevistas, los instrumentos de medición de pre, postratamiento y seguimiento.…”
Section: Materials Y Métodosunclassified
“…Está estructurada alrededor de un material educativo 26 y su efectividad ha sido reportada con anterioridad. [27][28][29] Dichos trabajos han mostrado reducción significativa de los síntomas de depresión. 27 Inicialmente, se diseñó como una intervención preventiva para mujeres en riesgo de depresión, pero debido a las características de la población a la que se quería beneficiar, se amplió a una intervención temprana, esto es, para mujeres con un diagnós-tico de depresión moderada, como se describe más adelante.…”
Section: Introductionunclassified